Penjatuhan Pidana Mati Sebagai Upaya Pemberantasan Tindak Pidana Korupsi - Sam Renaldy (Scholar Center, 2020)
This research is motivated by the failure to implement or never impose capital punishment for perpetrators of corruption in Indonesia. Not imposing maximum criminal sanctions for perpetrators of criminal acts of corruption makes it one of the factors in the difficulty of eradicating corruption in the country of Indonesia. The formulations of the issues are, First, how the legal arrangements regarding the criminal act of corruption based on the CorruptionLaw, Second, what are the provisionsof the death penalty for perpetrators of corruption based on the CorruptionLaw. This research uses normative legal methods. From the results it can be argued that: First, the legal arrangements regarding the eradication of the death penalty as a special criminal law have undergone many changes, with the aim of being more effective and providing maximum results in dealing with the eradication of corruption. Second, the provisions regarding the imposition of capital punishment for perpetrators of corruption in Indonesia are only regulated in one article, namely Article 2 paragraph (2) the elements and explanations of Article 2 paragraph (2) are very difficult to fulfill because there are no minimum and maximum limits for funds. for handling natural disasters that are corrupted by the perpetrators of criminal acts of corruption so that capital punishment can be imposed.